2004
DOI: 10.1002/jsfa.1884
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calcium and cellular permeabilization on the structure of the parenchyma of osmotic dehydrated ‘Granny Smith’ apple

Abstract: Calcium plays a very important role in the maintenance of quality in vegetable foods and it is used as a texturing agent to preserve the structure of minimally processed vegetables. The osmotic dehydration (OD) of 'Granny Smith' apple parenchyma by immersion in a sucrose solution allows us to obtain products with sensorial characteristics similar to those of fresh products, but it produces a loss of cellular integrity. Here we study the use of calcium as a possible preservative for the microstructural integrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 10 publications
(12 reference statements)
4
34
0
9
Order By: Relevance
“…Figure 5 shows that water loss was maximized by increasing both temperature and solution concentration. However, one must also consider that under these conditions the structure of the star-fruit may be permanently damaged either by destructuring of the cell wall due to high temperatures or even by high sugar concentrations, which increase plasmolysis and cause cell collapse (QUILES et al, 2004). It should also be observed that an increase in solution concentration at low temperatures reduced water loss due to the increase in viscosity, as previously mentioned, which did not occur for solids gain.…”
Section: Optimization Of the Osmotic Dehydration Processmentioning
confidence: 92%
“…Figure 5 shows that water loss was maximized by increasing both temperature and solution concentration. However, one must also consider that under these conditions the structure of the star-fruit may be permanently damaged either by destructuring of the cell wall due to high temperatures or even by high sugar concentrations, which increase plasmolysis and cause cell collapse (QUILES et al, 2004). It should also be observed that an increase in solution concentration at low temperatures reduced water loss due to the increase in viscosity, as previously mentioned, which did not occur for solids gain.…”
Section: Optimization Of the Osmotic Dehydration Processmentioning
confidence: 92%
“…El calcio se emplea para preservar la estructura de los tejidos vegetales Quiles et al, 2004;Saftner et al, 2003). A su vez, reduce la actividad respiratoria, la producción de etileno y el desarrollo de microorganismos (Saftner el al., 2003;Luna-Guzmán et al, 1999;LunaGuzmán & Barret, 2000).…”
Section: Justificación E Interés Del Estudiounclassified
“…Otros autores como Read et al, (1992), indican que las concentraciones de calcio libre en el citosol son del rango 30-200 nM, tres o cuatro órdenes de magnitud más bajos que los encontrados en los orgánulos intracelulares y en los espacios extracelulares (Felle, 1988;Giroy et al, 1990 El calcio es esencial para el mantenimiento de la estructura y el funcionamiento de las paredes y membranas celulares (Izumi & Watada, 1994). El mantenimiento de la estructura de la pared celular depende particularmente del enlace del calcio con los componentes pécticos de la lámina media (Grant et al, 1973;Poovaiah, 1986;Quiles et al, 2004). El complejo calcio-pectina actúa como un cemento intracelular que proporciona firmeza al tejido vegetal (Alonso et al, 1995).…”
Section: 53c Adición De Calciounclassified
See 2 more Smart Citations